Cooling effect of air movement of advanced air distribution under heating mode: Experimental analyses of stratum ventilation. (1st March 2023) - Zhang, Sheng; Cheng, Fanghui; Zhang, Xia; Lin, Zhang; Cheng, Yong
Abstract: The cooling effect of air movement significantly affects the energy-efficient provision of thermal comfort with advanced air distribution. Existing studies merely focus on the cooling effect of air movement under cooling mode. However, the cooling effect of air movement under heating mode can be different from that under cooling mode. This is because the cooling effect of air movement negatively and positively affects thermal comfort under heating and cooling modes respectively. This study experimentally investigates the cooling effect of air movement of stratum ventilation under heating mode. Stratum ventilation is representative of advanced air distribution with significant air movement for a proper airflow pattern under heating mode. A wide range of thermal conditions are tested with the air temperature of 19 °C–25 °C and air velocity of 0.1 m/s – 1.2 m/s. The thermal sensation votes and percentages of dissatisfied are simultaneously surveyed. Based on the experimental data, the cooling effect of air movement under heating mode is quantified, which is higher and lower than that under cooling mode in the cool and warm thermal environments respectively. Moreover, based on the upper and lower boundaries determined according to the percentage of dissatisfied of 10% predicted by an optimized model, the thermal comfort zone is prescribed under heating mode. For the thermal comfort zone, the cooling effect of air movement is compensated by the enhanced air temperature. This study contributes to improving the heating performances of advanced air distribution with the cooling effect of air movement. Highlights: CEAM under heating mode is different from that under cooling mode. CEAM is significantly affected by both air velocity and thermal sensation. Minimal PPD is reduced to 1.5%. Lower thermal comfort boundary is extended to air temperature of 17.5 °C.